Women in leadership: Exploring potential and challenges in the Islamic context - M. Ferry Irawan; Noptario Noptario; Muhammad Hulkin; Ts. Saiful Nazri bin Nordin (An-Nisa’ Journal of Gender Studies, 2024)
Muslim women's leadership has gained global attention. They actively pursue leadership positions while facing gender stereotypes and traditional perceptions. This study explores the factors of religious knowledge, emotional intelligence, and their experiences of challenges. The study aims to analyze the level of trust in the leadership potential of Muslim women, identify the main supporting factors (religious knowledge, multitasking, emotional intelligence), and explore the challenges arising from traditional interpretations of Islam and low public trust. This study employed a mixed-methods approach with 127 Muslim women leaders. Data were collected through interviews and surveys, analyzed using thematic analysis and descriptive statistics, and then integrated. The findings revealed three key points: (1) The leadership potential of Muslim women is demonstrated by high trust (63%) and optimism about future role enhancement (56%). (2) The main supporting factors include religious knowledge, multitasking, emotional intelligence, and perceived gender equality. (3) The main challenges stem from traditional interpretations of Islam and low trust in Muslim women's leadership, which limit acceptance. The study concludes that Muslim women's leadership is influenced by individual potential, supporting factors, and religious and social interpretive barriers, although progress in perceptions of gender equality in the workplace is evident. This study contributes to the development of human capital and intersectionality in Muslim women's leadership and offers practical recommendations including inclusive training, affirmative policies, and advocacy for more egalitarian religious interpretations.